Description of a new species of Schizodon (Characiformes: Anostomidae) from the upper rio Tapajós basin, Brazil - Britski, Heraldo A.; Garavello, Júlio C.; Ramirez, Jorge L. (Zootaxa, 2023)
A new species of Schizodon with five dark transverse blotches on the body and a large black blotch at the end of the caudal peduncle is described from the rio Arinos, upper rio Tapajós basin, in the Brazilian Amazon. The new species shares a color pattern composed by transverse brown bars and a caudal fin blotch with Schizodon fasciatus and S. trivittatus but possess twelve rows of scales around the caudal peduncle, a unique character among the species of genus.